Unbiased phage display screening identifies hidden malaria vaccine targets - Marcelo Jacobs-Lorena; Sung-Jae Cha (Emerging Microbes and Infections)
Malaria is among the deadliest infectious diseases. Over 200 million annual clinical malaria cases are reported and more than half a million people, mostly children, die every year. The most advanced RTS,S/AS01 vaccine based on the P. falciparum circumsporozoite protein (CSP), targets sporozoite liver infection but achieved modest efficacy. To reduce malaria death, novel malaria vaccine development is a high priority. Most malaria vaccine candidates target three infection steps: sporozoite liver infection, merozoite red blood cell (RBC) infection, and mosquito midgut infection. However, only few malaria vaccine candidates target specific parasite–host cell interactions. Our group has implemented the phage peptide-display approach to discover new parasite ligands and host cell receptors. Here we summarize our findings and discuss their potential for the development of novel vaccines.